Wind Engineering in the 21st Century - Vladimir Feranec (Communications - Scientific letters of the University of Zilina, 2000)
Progress in wind engineering during last 3-5 decades is described in this paper, from the existence of wind tunnels with the simulated atmospheric boundary layer and introducing random processes in wind load on buildings and structures. State of the art is presented from the First International Conference on Wind Effects on Buildings and Structures in U. K. (1963) together with some visions for the future. Some remarks are also devoted to wind engineering research in the Department of Structural Mechanics, Civil Engineering Faculty, University of Žilina [1] – [31].